Comparison of extraction and clean-up methods for comprehensive screening of organic micropollutants in fish using gas chromatography coupled to high-resolution mass spectrometry. (January 2022) - Dubocq, Florian; Bæringsdóttir, Bergdís Björk; Wang, Thanh; Kärrman, Anna
Abstract: Monitoring the vast number of micropollutants in the environment by using comprehensive chemical screening is a major analytical challenge. The aim of this study was to evaluate a comprehensive analysis method for screening purposes of fish muscle samples by comparing sample preparation methods for a broad range of mid-to non-polar contaminants. Five extraction and three clean-up methods were evaluated for the analysis of 60 compounds with a log Kow range between 0.8 and 8.3 in fish. Both fresh and freeze-dried muscle tissue and extraction sodium sulphate blanks were included to assess recoveries and matrix effects. The performance of the different methods was evaluated using both comprehensive target and nontarget analysis using high resolution mass spectrometry (HRMS). The results showed that open-column and ultrasonication extractions (recoveries mostly between 20 and 160 %) resulted in higher recoveries than accelerated solvent extraction (ASE) (recoveries mostly between 20 and 80 %) and bead mixer homogenization extractions (recoveries between 0 and 50 % for the whole Kow range). Multilayer silica was the clean-up method resulting in the lowest matrix effects and highest recoveries, however some compounds (mostly pesticides) were denatured under the acidic conditions used. The convenient and time efficient ultrasonication extraction followed by deactivated silica clean-up proved to be promising for both target and nontarget approaches. The large difference in recoveries and number of detected peaks using target and nontarget approaches between fresh and freeze-dried fish seen for all methods calls for careful consideration, and further studies are needed to improve performance for screening of mid-to non-polar compounds in freeze-dried fish. Graphical abstract: Image 1 Highlights: Comparison of extraction and clean-up methods for wet weight and freeze-dried fish. Determination of recoveries and matrix effects for 60 relevant pollutants. Sonication extraction followed by deactivated silica is the most suitable method. Open-column and ASE extraction and multilayer silica can also be suitable. Comparison of total and halogenated detected features applying nontarget approach.